DAMPAK PANDEMI COVID-19 BAGI PENDIDIKAN INDONESIA - Tristaningrat, Made Adi Nugraha (Maha Widya Bhuwana: Jurnal Pendidikan, Agama dan Budaya, 2021)
This study aims to analyze several articles related to the impact of the COVID-19 pandemic on the learning process in Indonesia. The research method used in this article uses several literature articles in a meta-analysis that aims to analyze various journals related to the impact of COVID-19 on learning in Indonesia. Learning at all levels has changed due to the COVID-19 pandemic, so that from this impact analysis, it is hoped that solutions can be found in the future. Online/online learning is carried out using several applications such as google, google classroom, zoom. The impact that occurs is divided into elements in learning, namely educators and students. The impact felt by educators is not adapting to the new learning process, educators are still accustomed to conventional learning so that changing learning to be bold/ online becomes difficult and is considered difficult. For many students who feel the experience when doing online learning and the internet which is still an obstacle because it causes a lot of information received is not intact.Â